Optimizing Heat Treatment of Fruit Juices: Ensuring Quality Through Reduced Temperature - Sarlak,Shahram (2025)
This study evaluated the efficacy of reduced-temperature pasteurization in preserving the nutritional, sensory, and microbial integrity of two fruit juice products: a standard orange juice and a probiotic mango juice enriched with Lactiplantibacillus plantarum 299v, conducted at Österlenmejeriet AB in Lunnarp, a subsidiary of Danone. Laboratory-scale thermal treatments were applied at temperatures ranging from 70°C to 90°C with varying holding times. In orange juice, complete microbial inactivation was achieved at temperatures ≥80°C, while lower temperatures (e.g., 75°C for 45 seconds) effectively minimized vitamin C degradation and better preserved sensory attributes such as taste and aroma. In probiotic mango juice, microbial safety was maintained across all conditions, with no detectable levels of Enterobacteriaceae, yeasts, or molds. Importantly, probiotic viability remained above the therapeutic threshold (10⁷ CFU/mL) in treatments up to 85°C, with a notable decline observed at 90°C. Vitamin C degradation exhibited a positive correlation with both temperature and exposure time. The lowest degradation occurred at 70°C, where vitamin C loss remained below 5.2 mg/100 g even after 120 seconds. In contrast, degradation exceeded 7.5 mg/100 g at 90°C after just 20 seconds, indicating a rapid reduction of ascorbic acid content under severe thermal conditions. Post-thermal processing, °Brix values generally remained stable or slightly increased, with the final increment in probiotic mango juice attributed to soluble solids from the added oat base. Similarly, a slight pH increase (decrease in acidity) was observed post-treatment, particularly above 80°C. Additionally, vitamin C retention during storage was significantly higher in samples treated below 80°C. °Brix and pH remained stable across processing and storage, indicating overall product quality preservation. These findings demonstrate that optimized sub-pasteurization treatments can achieve microbiological safety while enhancing nutritional and functional quality in juice products, supporting their industrial application and sustainability goals.
Keywords: Food engineering nutrition and food chemistry; reduced-temperature pasteurization; vitamin C retention; probiotic viability; thermal processing; fruit juice quality; microbial safety; probiotic mango juice; prange juice processing